Ischemic preconditioning and exercise performance: are the psychophysiological responses underestimated? - Marocolo, M.; Hohl, R.; Arriel, R. A.; Mota, G. R. (European Journal of Applied Physiology, 2023)
The findings of the ischemic preconditioning (IPC) on exercise performance are mixed regarding types of exercise, protocols and participants' training status. Additionally, studies comparing IPC with sham (i.e., low-pressure cuff) and/or control (i.e., no cuff) interventions are contentious. While studies comparing IPC versus a control group generally show an IPC significant effect on performance, sham interventions show the same performance improvement. Thus, the controversy over IPC ergogenic effect may be due to limited discussion on the psychophysiological mechanisms underlying cuff maneuvers. Psychophysiology is the study of the interrelationships between mind, body and behavior, and mental processes are the result of the architecture of the nervous system and voluntary exercise is a behavior controlled by the central command modulated by sensory inputs. Therefore, this narrative review aims to associate potential IPC-induced positive effects on performance with sensorimotor pathways (e.g., sham influencing bidirectional body-brain integration), hemodynamic and metabolic changes (i.e., blood flow occlusion reperfusion cycles). Overall, IPC and sham-induced mechanisms on exercise performance may be due to a bidirectional body-brain integration of muscle sensory feedback to the central command resulting in delayed time to exhaustion, alterations on perceptions and behavior. Additionally, hemodynamic responses and higher muscle oxygen extraction may justify the benefits of IPC on muscle contractile function.